Preparation and biophysical characterization of recombinant Pseudomonas aeruginosa phosphorylcholine phosphatase - Beassoni, Paola Rita (2010)
Pseudomonas aeruginosa infections constitute a widespread health problem with high economical and social impact, and the phosphorylcholine phosphatase (PchP) of this bacterium is a potential target for antimicrobial treatment. However, drug design requires high-resolution structural information and detailed biophysical knowledge not available for PchP. An obstacle in the study of PchP is that current methods for its expression and purification are suboptimal and allowed only a preliminary kinetic characterization of the enzyme. Herein, we describe a new procedure for the efficient preparation of recombinant PchP overexpressed in Escherichia coli. The enzyme is purified from urea solubilized inclusion bodies and refolded by dialysis. The product of PchP refolding is a mixture of native PchP and a kinetically-trapped, alternatively-folded aggregate that is very slowly converted into the native state. The properly folded and fully active enzyme is isolated from the refolding mixture by size-exclusion chromatography. PchP prepared by the new procedure was subjected to chemical and biophysical characterization, and its basic optical, hydrodynamic, metal-binding, and catalytic properties are reported. The unfolding of the enzyme was also investigated, and its thermal stability was determined. The obtained information should help to compare PchP with other phosphatases and to obtain a better understanding of its catalytic mechanism. In addition, preliminary trials showed that PchP prepared by the new protocol is suitable for crystallization, opening the way for high-resolution studies of the enzyme structure. © 2010.